(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the principle of unity of diagnosis and correction. Diagnostics not only precedes psychological impact, but also serves as a means of monitoring changes in personality, emotional states, behavior, and cognitive functions during correctional work, as well as a tool for evaluating it.